2011
DOI: 10.1103/physrevlett.107.186602
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Power in Dual-Gated Bilayer Graphene

Abstract: The thermoelectric power of a material, typically governed by its band structure and carrier density, can be varied by chemical doping that is often restricted by solubility of the dopant. Materials showing large thermoelectric power are useful for many industrial applications, such as the heat-to-electricity conversion and the thermoelectric cooling device. Here we show a full electric-field tuning of thermoelectric power in a dual-gated bilayer graphene device resulting from the opening of a band gap by appl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 38 publications
5
46
0
Order By: Relevance
“…In particular, its high mobility, which due to the weak electron-phonon interaction persists up to room temperature, can be orders of magnitude higher than in other 2D thermoelectric materials, such as semiconducting transition metal dichalcogenides (13)(14)(15)(16). Theoretical and experimental studies show that the Seebeck coefficient in graphene could reach values comparable to that in bulk semiconductors by decreasing the carrier density (17)(18)(19)(20)(21)(22)(23). The combination of graphene's large mobility and competitive Seebeck coefficient result in large power factor and large active cooling.…”
Section: ·Kmentioning
confidence: 99%
“…In particular, its high mobility, which due to the weak electron-phonon interaction persists up to room temperature, can be orders of magnitude higher than in other 2D thermoelectric materials, such as semiconducting transition metal dichalcogenides (13)(14)(15)(16). Theoretical and experimental studies show that the Seebeck coefficient in graphene could reach values comparable to that in bulk semiconductors by decreasing the carrier density (17)(18)(19)(20)(21)(22)(23). The combination of graphene's large mobility and competitive Seebeck coefficient result in large power factor and large active cooling.…”
Section: ·Kmentioning
confidence: 99%
“…30 Moreover, previous experimental results showed that exfoliated single-layer and bilayer graphene showed a high Seebeck coefficient of 50-100 µV K -1 . [31][32][33] However, the exceedingly high thermal conductivity of graphene (2500-5300 W m -1 K -1 ) 34,35 makes it a poor contestant for TE property. An effective method is to combine a low thermal conductivity material with high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Furthermore, this results in the enhancement of the thermoelectric power in bilayer graphene. 34,35 Due to the Mexican-hat dispersion relations, there are two kinds of the gap (Fig. 1(d)).…”
Section: Resultsmentioning
confidence: 99%